IMPLEMENTASI KEBIJAKAN PENINGKATAN KUALITAS PERMUKIMAN MELALUI KONSOLIDASI TANAH VERTIKAL DI TANAH TINGGI JAKARTA PUSAT - Chairunnisa Rahimah Yusa; Hardi Warsono (Journal of Management and Public Policy, 2026)
Urban slum settlements represent a structural challenge that demands innovative policy approaches. This study examines the implementation of settlement quality improvement policy through the Vertical Land Consolidation (VLC) program "Rumah Cinta Damai" in Tanah Tinggi Village, Central Jakarta is a pilot project transforming densely populated slum areas into decent vertical housing with legal ownership certainty for affected residents. This research employs a qualitative descriptive approach through in-depth interviews, field observation, and documentation. Implementation analysis is grounded in Ministerial Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 12 of 2019 on Land Consolidation, while driving and inhibiting factors are analyzed using Van Meter and Van Horn's theoretical framework (1975). The findings indicate that the VLC program successfully improved housing quality through a series of stages, including intensive community preparation, community-based institutional formation, housing unit distribution based on the Proportional Percentage Value (PPV) system, and multi-stakeholder collaboration among government, private sector, and community actors. Driving factors include clear policy standards and objectives, adequate resource availability, solid interagency coordination, and persuasive approaches by field implementers. Inhibiting factors identified include policy communication that has yet to bridge the knowledge gap among residents, overlapping programs, dependency on Corporate Social Responsibility (CSR) funding, and the absence of specific Technical Guidelines for VLC implementation. This research recommends the formulation of comprehensive technical regulations, strengthening of sustainable financing schemes, and the development of a structured post-construction monitoring and evaluation system.